Endüstriyel tesislerde kullanılan buharlı bileşik ısı güç sistemleri - İmal, Muharrem (Fen Bilimleri Enstitüsü, 1991)
Birleşik ısı ve güç çevrimlerinin endüstride kullanımının yaygınlaşması bu konudaki araştırmalara yeni boyutlar kazandırmaktadır. Bu durum göz ününe alınarak endüstride kullanılan buharlı birleşik ısı -güç çevrimleri ne ait termodinamik ve ekonomik çözümlemelerin yapıldığı bu çalışmada beş bölüm bulunmaktadır. Birinci bölümde, yapılan çalışmanın amacı açıklanmış, literatürdeki yerine ve önemine değinilmiştir. Konu ile ilgili kabullerden bahsedilmiştir. ikinci bölümde, buharlı güç çevrimleri hakkında genel bilgi verilmiştir. Çevrimlere ait T-s ve akis diyagramlarının yer aldığı bu bölümde çalışmada dikkate alınan değişkenlerin değişim aralığından bahsedilmiştir. Uçüncü bölümde, termodinamik çözümleme yapılarak, kısmi ve tam yükte ısı ve elektirik enerjisinin değişimi ile proses için gereken ısı enerjisi değeri hesaplanmıştır Dördüncü bölümde yakıt fi ati arı ve yakıt türleri yanısıra isletmelerin ihtiyaç duyduğu güç değerleri ve çalışma süreleri esas alınarak bu çevrimlerin ekonomik analizi yapılmıştır. Son bölümde sonuçların grafiklerle kıyaslama ve tartışması yapılarak her iki çevrime ait değişik değerlerin irdelemesi yapılmıştır.

Thermodynamic models for twoprocess heating, cogeneration steam cycles were developed in this study. These cycles are an extraction-condensing turbine cycle and a back pressure turbine cycle. Heat and electric outputs were calculated for inlet conditions ranging from 3 MPa, 250 C to 12 MPa, 535 C and process heat supply temperatures ranging from 80 C to 160 C. Furthermore, the performance of these cycles at 0 to 100 percent of their maximum heat outputs were examined. A simple method of economic analysis based on the annual costs was developed. This method can take part load into consideration. An extraction-condensing system and a back pressure system were compared by using this method. Process heating with cogeneration is a thermodinamically effective way of supplying heat and power to the industry. In a central plant, fuel can be burned more efficently, environmental controls can be applied more easily and economies of scale can be used to advantage. Furthermore, producing electricity as a byproduct in such plants is less expensive than producing electricity in power stations. In the extraction-condensing type, steam is expanded to condenser pressure and an extraction is made at the saturation pressure corresponding to the process heat supply temperature. In the back pressure type, steam is expanded only to the saturation pressure correspoding to the process heat supply temperature. The extraction-condensing turbines have the advantage that the electric output can be increased at partial heat loads. On the other hand, back- pressure turbines have a simpler mechanism of load control and lower initial costs. Detailed thermodynamic analysis of these systems appears to be lacking [14]-. For example, information on the variation of heat and electric outputs and thermal efficiencies of different configurations with changes in load and inlet steam conditions is essantial for the initial planning stage. vi In this study, computer modelling and simulation of two steam turbine based cogeneration cycles is made. Nu merical experiments were performed for various steam inlet conditions. Heat and electric outputs of cycles, heat input to the cycles and various parameters based on these thermodynamic quantities were calculated at full load and part load conditions. Partial loads ranging from 0 to 100 percent of full load were considered for the extraction-condensing cycle and partial loads of 37.5 to 100 percent were considered for the back pressure cycle. Thermodynamic Analysis The extraction-condensing turbine cycle consists of steam generator, turbine, condenser, heating condenser, feedwater heaters and pumps. The following assumptions are made regarding this cycle: The condenser is assumed to operate at 10 kPa. Extractions from the turbine to the feedwater heaters, heating condenser and the condenser is assumed to occur with a pressure loss equal to 5 persent of the exraction pressure. Pressure loss in the steam generator is assumed to be 25 percent of the turbine inlet pressure. Enthalpy rise of the feedwater is taken as 70 percent of the theoretically optimum value [13- This value is given by Ahopt = n/n+1 (hab - he) (1) where: n is the number of feedwater heaters, hs*> is the boiler drum satureted liquid enthalpy he is the enthalpy of satureted liquid leaving the condenser The loses in the expansion process through the turbine are accounted for by using an isentropic efficiency, r/, defined as : hi- ho r, = - t- r (2) h>- - hos where : hi is the enthalpy before expansion ho is the enthalpy after expansion hos is the enthalpy after an isentropic expansion This value is taken as 0.8 for the high pressure section of the turbine. The isentropic expansion efficiency for the flow between the heating condenser extraction and the turbine exhaust decreases linearly from 0.8 to 0.5 as the flow to the condenser decreases. Isentropic efficiency or compression in all of the pumps is asumed to be 0.7. vii The calculations performed in the computer program are summarized in the block diagram of figure 1. Application of the first law of thermodynamics and the conservation of mass to each of the components of the cycle yield the exraction mass flows, work in the turbines and in the pumps, heat transfer in the boiler, heating condenser and in the condenser. Heat output is assumed to be primary output from the cycle. Electric output is considered to be a byproduct. Variation of the heat output is achieved by controlling the flow passing through the condenser. At 100 percent heat output, only the cooling steam flows to the condenser. At no heat output, there is no flow through the heating condenser. Cycle calculations have been performed for 100, 75, 50, 25, and 0 percent of the maximum heat output. Assumptions calculation procedures outlined above for the extraction-condensing cycle also apply for back- pressure cycle. The control of heat output, however, is different. The heat output of the back pressure cycle is varied by changing the mass flow rate through the turbine. Calculations have been performed for 100 to 37.5 percent of the maximum heat output. Properties of water required in the computer programs were computed using the equation and procedures given in [3]- Economic Analysis It is the economic consideration which will determine whether or not a cogeneration plant should be built. A simple method is presented here for determining the economic feasibility of a cogeneration plant. In this method all costs and revenues are expressed on an annual basis for comparison. Two assumption are made. First the heat demand is assumed to be supplied by other means if a cogeneration plant is not built. Therefore only the additional or incremental cost is considered. This includes the turbo generator set, condensers, feedwater heaters, steam generators, additional piping, fuel handling, exhaust cleaning measures, building and consruction costs as well as engineering cost. The second assumption is that all of the byproduct electricity produced can be utilised. A numerical example using this method shows that an extinction condensing cycle should bepreferred if the system is to operate at partial heat loads for long periods of time. Back-pressure cycle will be economically feasible only if the system operates at full load more than 90 percent of the time. However the most economic operation for the extraction-condensing cycle is also realized at full load. vm Results Results of the computer simulation of the two cycles discussed above. The key parameters on which the results are based, are explained below. Heat output per unit mass of steam entering the turbine has a maximum value for a given throttle condition and process heat supply temperature. Heat output from the cycle for a given set of turbine inlet conditions was varied as explained in the thermodinamic a na lysis. It was also found that the thermal efficiency of these cycles, defined as net work output over the heat input. Increasing the process heat supply temperature decreases the electric to heat ratio and the electric out put, increases the heat output. IX Enter the type of the system Turbine inlet pressure and temperature Process heat supply temperature Deter mine feedwater enthalpy rise and Turbine exraetion pressure Determine for the case of no heat output mass flow to the feed water heaters and the condenser r* Select a heat load as a percent of full load L-. Determine mass flows to the feedwater heaters, process heating condenser, condenser, net work, electric output heat output, heat input Figure 1. Block diagram of calculation procedure
Thermodynamic and economic analysis of combined heat and power (cogeneration) steam cycles
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1991
Keywords: Endüstri sektörü; Isı enerjisi; Kojenerasyon; Industry sector; Heat energy; Cogeneration